Üniversite Öğrencilerinin İnternet Üzerinden Alışverişlerine İlişkin Tutum ve Davranışların Önerilen Bir Yapısal Eşitlik Modeliyle Araştırılması (A Proposed Structural Equation Model Research On Attitudes And Behaviours Of University Students Regarding Internet Shopping) - Erkan ARI; Veysel YILMAZ; Murat DOĞAN (Yönetim ve Ekonomi, 2015)
In the study it is aimed to bring out the factors affect the attitudes and behaviors of University Students' internet shopping by the help of Planned Behavior Theory. For this purpose, a survey was implemented on 385 students of Eskişehir Osmangazi University in the academic year 2014-2015. In analyzing the data, Structural Equation Model (SEM) was used in order to determine the relationship between the factors that influence the attitudes and behaviors of university students while making internet shopping and in order to evaluate the coherence of the model. As the result of SEM analysis it was concluded that attitude, perceived behavioral control and satisfaction variables affect the intention towards behavior positively and intention towards behavior affect internet shopping behavior positively.